Assessing gaps in marine conservation in California. Issue 5 (1st June 2006) - Gleason, Mary G.; Merrifield, Matt S.; Cook, Chuck; Davenport, Audrey L.; Shaw, Rebecca
Abstract : Implementation of marine conservation strategies lags far behind terrestrial conservation efforts. Quantifying what is protected and what is not, or "gap analysis", helps to show just how much work there is to do; systematic conservation planning provides guidance on how to best fill those gaps. We conducted the first marine gap analysis for California by comparing distributions of major ecosystems and habitats with existing marine protected areas. Less than 0.3% of state and federal waters (to the bottom of the continental slope) are within no‐take or limited‐take marine protected areas (MPAs). With few exceptions, less than 5% of marine habitats are within no‐take or limited‐take MPAs that afford a high level of ecosystem protection. Efforts to create new MPAs to include representative habitats will help to fill some gaps, but additional conservation strategies, such as ocean zoning and ecosystem‐based management of fisheries, are needed to balance protection and sustainable use of marine biodiversity.